The redox-active site of thioredoxin is directly involved in apoptosis signal-regulating kinase 1 binding that is modulated by oxidative stress - Psenakova, Katarina; Hexnerova, Rozalie; Srb, Pavel; Obsilova, Veronika; Veverka, Václav; Obsil, Tomas (The FEBS journal, 2020)
Apoptosis signal-regulating kinase 1 (ASK1) is a ubiquitously expressed mitogen-activated protein kinase kinase kinase 5, which mediates various stress signals including oxidative stress. The catalytic activity of ASK1 is tightly controlled by oligomerization and binding of several cofactors. Among these cofactors, thioredoxin stands out as the most important ASK1 inhibitor, but only the reduced form of thioredoxin inhibits ASK1 by direct binding to its N-terminal domain. In addition, oxidation-driven thioredoxin dissociation is the key event in oxidative stress-mediated ASK1 activation. However, the structural mechanism of ASK1 regulation by thioredoxin remains unknown. Here, we report the characterization of the ASK1 domain responsible for thioredoxin binding and its complex using NMR spectroscopy and chemical cross-linking, thus providing the molecular basis for ASK1: thioredoxin complex dissociation under oxidative stress conditions. Our data reveal that the N-terminal domain of ASK1 adopts a fold resembling the thioredoxin structure while retaining substantial conformational plasticity at the thioredoxin-binding interface. Although oxidative stress induces relatively moderate structural changes in thioredoxin, the formation of intramolecular disulfide bridges leads to a considerable conformational rearrangement of the thioredoxin-binding interface on ASK1. Moreover, the cysteine residue at position 250 of ASK1 is the key element of this molecular switch. Finally, our results show that the redox-active site of thioredoxin is directly involved in ASK1 binding that is modulated by oxidative stress, thereby identifying a key target for the structure-based drug design.
Keywords: apoptóza; inhibitory proteinkinas; oxidační stres; vazebná místa; Thioredoxins; Apoptosis; Oxidative Stress; lidé; MAP Kinase Kinase Kinase 5; Models, Molecular; magnetická rezonanční spektroskopie; oxidace-redukce; MAP kinasa-kinasa-kinasa 5; molekulární modely; Protein Kinase Inhibitors; Oxidation-Reduction; thioredoxiny; Magnetic Resonance Spectroscopy; Binding Sites; Humans